Analysis of Van Dijk's Critical Discourse on the Lyrics of the Song "Komang" by Raim Laode - Hasminur Hasminur; Charlina Charlina; Mangatur Sinanga (International Journal of Language and Ubiquitous Learning, 2024)
Background. Van Dijk's critical discourse analysis is an approach used to uncover the power of ideology and power in texts. The lyrics of the song "Komang" by Raim Laode are the object of study because they contain social and cultural messages that are relevant to today's society. Purpose. This study aims to analyze how the lyrics of the song "Komang" reflect the strength of ideology and power structure in society through Van Dijk's critical discourse analysis approach. The specific purpose of this study is to understand the hidden meaning and social context presented in the lyrics of the song. Method. The research method used is the analysis of Van Dijk's critical discourse, which involves three main dimensions: text, social cognition, and social context. The data was collected through the analysis of the lyrics of the song "Komang" with a focus on the text structure, rhetorical strategy, and socio-cultural context that influenced it. Results. The results of the analysis show that the lyrics of the song "Komang" contain social criticism of injustice and inequality in society. Through the use of poetic and symbolic language, Raim Laode succeeded in conveying important messages about struggle and hope. The lyrics also reflect the ideology of resistance to oppressive power structures. Conclusion. The lyrics of Raim Laode's song "Komang" are not just a work of art, but also a form of strong social criticism. Van Dijk's critical discourse analysis reveals that the lyrics are loaded with ideological meanings and criticisms of social injustice. This research provides insight into how music can be an effective medium to voice social issues and influence people's thinking.